(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Synthesis of organoselenium multidentate ligands having 24- and 28-membered ring in dry acetonitrile under inert atmosphere has been carried out and studied their reactivity towards NiCl2. The reaction has been carried out at room temperature. These ligands on coordination with NiCl2 in, 1:2 molar ratio in CH3OH, its produced green colored compound 1 and 2. The mononuclear complexes 1 and 2 are found to have [Se(CH2)nN=CPhC6H2(O)(4-CH3)PhC=O2Ni] (where n = 2, 3) molecular composition with the elimination of CH3COOH and bis(aminoalkyl) selenide. The above compound 1and 2, Ni(II) binds in a bidentate mode (N2O2) after the hydrolysis of two azomethine bonds (C=N) of the Schiff base compound. The complexes 1 and 2 have been characterized by various spectroscopic techniques such as ESIMS, IR, UV-Visible, cyclic voltammeter and conductance measurements.